LOWE-BICKEL SYNDROME IN CHILDREN (World Bulletin of Public Health, 2025)
Lowe-Bickel syndrome is a rare hereditary disease that affects various organs and systems. Three main signs of the disease are identified: congenital cataract, profound intellectual disability, and kidney pathology leading to slowly progressive renal failure. The cause of Lowe syndrome is mutations in the OCRL gene, which encodes one of the enzymes involved in the metabolism of inositol phosphates. Mutations in this gene are also associated with Dent's syndrome, which has overlapping manifestations with Lowe syndrome but expressed to a lesser degree. The disease follows an Xlinked pattern of inheritance, which is why it primarily affects males. This paper discusses the clinical features, treatment, and outcomes of the Lowe syndrome in children. We describe the observation of two boys from the same family with Lowe syndrome, whose kidney involvement was characterized by Fanconi syndrome.
Keywords: children; Lowe-Bickel syndrome